The Moment Criterion of Anthropomorphicity of Prosthetic Feet as a Potential Predictor of Their Functionality for Transtibial Amputees - Pitkin, Mark (Biomimetics (Basel, Switzerland), 2023)
The purpose of this paper is to discuss a new quantitative mechanical parameter of prosthetic feet called the Index of Anthropomorphicity (IA), which has the potential to be adopted as an objective predictor of their functionality. The objectives are to present the research findings supporting the introduction of IA and unify previous results into a coherent theory. The IA is founded on the moment criterion of the anthropomorphicity of prosthetic feet. The term “anthropomorphicity” is defined for this application. Studies with a small number of human subjects and prostheses have shown that the value of the parameter is positively correlated with patient comfort and with the restoration of certain normal gait characteristics. Confirmatory studies with controlled human trials and mechanical tests with a wider selection of prosthesis types can give prosthesis manufacturers a new criterion to follow in the design process, and prosthetists may use the IA for selecting more suitable prostheses for a patient’s comfort and health.